2018
DOI: 10.1105/tpc.17.00764
|View full text |Cite
|
Sign up to set email alerts
|

The Biotrophic Development of Ustilago maydis Studied by RNA-Seq Analysis

Abstract: The corn smut fungus Ustilago maydis is a model organism for elucidating host colonization strategies of biotrophic fungi. Here we performed an in depth transcriptional profiling of the entire plant-associated development of U. maydis wild-type strains. In our analysis we focused on fungal metabolism, nutritional strategies, secreted effectors and regulatory networks. Secreted proteins were enriched in three distinct expression modules corresponding to stages on the plant surface, establishment of biotrophy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
362
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(375 citation statements)
references
References 134 publications
13
362
0
Order By: Relevance
“…S5). The abundance of T. thlaspeos reads in infected samples was low (0.18–0.28%), which is in agreement with the early phase of maize infection by U. maydis , when the fungal hyphae have not started proliferating and the coverage is < 0.5% (Lanver et al ., ). U. maydis then proliferates massively at the local infection site, while T. thlaspeos grows along the vasculature, resulting in relatively low levels of fungal biomass.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…S5). The abundance of T. thlaspeos reads in infected samples was low (0.18–0.28%), which is in agreement with the early phase of maize infection by U. maydis , when the fungal hyphae have not started proliferating and the coverage is < 0.5% (Lanver et al ., ). U. maydis then proliferates massively at the local infection site, while T. thlaspeos grows along the vasculature, resulting in relatively low levels of fungal biomass.…”
Section: Resultsmentioning
confidence: 97%
“…Subsequently, fungal hyphae proliferate inside the apoplast and/or grow through host cells, establishing an intimate contact zone for the exchange of nutrients and proteins. Functional genomic analyses of the grass smut fungi U. maydis, Sporisorium reilianum and U. hordei have greatly contributed to our understanding of smut infection and the associated host responses (K€ amper et al, 2006;Brefort et al, 2009;Ghareeb et al, 2015;Lanver et al, 2018). In short, these studies have revealed different repertoires of conserved and host-adapted effector proteins (Okmen & Doehlemann, 2014;Lanver et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The oligopeptide transporter (OPT) genes are more numerous in rust fungi than in other basidiomycetes and have been shown to be highly expressed during host infection and in haustoria of rust fungi (Duplessis et al, 2011a;Garnica et al, 2013). Recently, OPT genes were associated with virulence in the smut fungus Ustilago maydis, suggesting that extracellular peptides represent an important source of nutrients for the fungus (Lanver et al, 2018). So far, no functional characterization of OPT has been conducted in rust fungi.…”
Section: Nutrient Uptake From the Hostmentioning
confidence: 99%
“…To shed light on the functional implication of the translocation of the HEG and subsequent mutations we (i) assessed the expression profile of these genes and (ii) generated a deletion strain and phenotyped it. For the expression analysis we relied on a previously published RNASeq data set (Lanver et al 2018), from which we extracted the expression profiles of genes in the telomeric region of chromosome 9 ( Figure 5A). While the expression of UMAG_11064 remained close to zero in the three replicates, expression of UMAG_11065 increased during plant infection.…”
Section: Functional Characterizationmentioning
confidence: 99%